Embolizacja wewnątrznaczyniowa jako jedna z metod leczenia krwawienia podpajęczynówkowego z pękniętego tętniaka = Endovascular embolization as a method in treatment of subarachnoid hemorrhage from ruptured aneurysm - Kamila Woźniak; Dorota Ratuszek-Sadowska; Maciej Śniegocki (Kazimierz Wielki University, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. Embolizacja wewnątrznaczyniowa jako jedna z metod leczenia krwawienia podpajęczynówkowego z pękniętego tętniaka = Endovascular embolization as a method in treatment of subarachnoid hemorrhage from ruptured aneurysm. Journal of Education, Health and Sport. 2016;6(8):681-687. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61141 http://ojs.ukw.edu.pl/index.php/johs/article/view/3796       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016.     Embolizacja wewnątrznaczyniowa jako jedna z metod leczenia krwawienia podpajęczynówkowego z pękniętego tętniaka   Endovascular embolization as a method in treatment of subarachnoid hemorrhage from ruptured aneurysm   Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1  1.        Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2.        Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu     Streszczenie   Pod nazwą krwawienie podpajęczynówkowe kryje się wynaczynienie krwi z pękniętego, zmienionego naczynia (tętniaka) do przestrzeni podpajęczynówkowej mózgowia i/lub rdzenia kręgowego. Przestrzeń podpajęczynówkowa to przestrzeń zawarta pomiędzy oponą miękką a oponą pajęczą (pajęczynówką). Zawiera ona płyn mózgowo-rdzeniowy. W oparciu o dane z piśmiennictwa szacuje, że krwawienie podpajęczynówkowe jest przyczyną około 10-12% wszystkich śródczaszkowych incydentów naczyniowych. Nieleczone krwotoki podpajęczynówkowe są przyczyną wysokiej śmiertelności, dlatego tak ważne z punktu widzenia klinicznego jest szybkie postawienie diagnozy i wdrożenie odpowiedniego leczenia operacyjnego lub embolizacji.   Słowa kluczowe: krwawienie podpajęczynówkowe, embolizacja wewnątrznaczyniowa, tętniak.   Abstract   Under the name of subarachnoid hemorrhage hidden extravasation of blood from ruptured, amended vessel (aneurysm) in the subarachnoid space of the brain and / or spinal cord. Subarachnoid space is the space contained between the subependymoma and the arachnoid. It contains the cerebrospinal fluid. Based on data from the literature it estimates that subarachnoid hemorrhage is the cause of about 10-12% of all intracranial vascular events. If left untreated, subarachnoid hemorrhages are the cause of high mortality, so it's important from the clinical point of view is a fast diagnosis and implementation of appropriate treatment - surgery or embolization.   Key words: subarachnoid hemorrhage, endovascular embolization, aneurysm.